2008
DOI: 10.1097/mpa.0b013e31816618a4
|View full text |Cite
|
Sign up to set email alerts
|

Exon III Splicing of Fibroblast Growth Factor Receptor 1 Is Modulated by Growth Factors and Cyclin D1

Abstract: This study demonstrated for the first time that FGFR1-IIIb and FGFR1-IIIc are coexpressed and that the FGFR1-III isoformsare differentially regulated by growth factors and cyclin D1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The establishment of the FGFR1-IIIb and -IIIc PANC-1 clones over-expressing the full-length cDNA of human FGFR1-IIIb or -IIIc expressed in a modified pSVK3 vector under the control of the simian virus 40 early promotor in a stable manner was described earlier (Liu et al, 2007b;Chen et al, 2008).…”
Section: Establishment Of Cell Clones Over-expressing Fgfr1-iii Variantsmentioning
confidence: 99%
“…The establishment of the FGFR1-IIIb and -IIIc PANC-1 clones over-expressing the full-length cDNA of human FGFR1-IIIb or -IIIc expressed in a modified pSVK3 vector under the control of the simian virus 40 early promotor in a stable manner was described earlier (Liu et al, 2007b;Chen et al, 2008).…”
Section: Establishment Of Cell Clones Over-expressing Fgfr1-iii Variantsmentioning
confidence: 99%
“…Furthermore, more recently, it has been reported that the inhibition of cyclin D1 using constitutively active cyclin D1 antisense cDNA expression vector resulted in the suppression of FGFR 1-IIIc mRNA expression, one of the alternative splice variants of FGFR 1, in human pancreatic cancer PANC-1 cells (Chen et al, 2008). In the present study, we also found that the expression of FGFR 1 is up-regulated in E2F-1-overexpressing LoVo cells, and down-regulated in pRB-overexpressing HT1080 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The summarized results are shown for clone P19-13 in Figure 1 (BYD) and were shown for clone P19-22 previously. 23 …”
Section: Establishment Of Tet-inducible Cyclin D1 Antisense Expressinmentioning
confidence: 99%